Articulating Beliefs: A Comprehensive Analysis of English Teachers' Perspectives on Grammar Teaching - Wati, Siska Oktawidya; Syarif, Hermawati; Zainil, Yetti (Journal of English Language and Education, 2023)
Teacher beliefs are about how teachers conceptualize their work in classroom. Based on the theories, teacher beliefs is an important element in improving the quality of educational  practice.  Therefore,  the  purposes  of  this  study  are  to describe  the  teachers‟  beliefs  and  to  investigate  how  the  teachers “practice of teaching grammar in classroom. The research method used is descriptive qualitative. The subjects of this study were two English teachers who were experienced in teaching English at  SMPN 1 Harau. The instruments used are interview, field notes, and documents. The technique of data analyses used the Mile and Huberman model. Based on the result of the study the data show that teachers beliefs that grammar is important because it effects on how students make the correct sentence. There are five factors that support the beliefs, lesson plan, teaching method, teaching procedure, sources of teaching materials, the teachers and students roles. However, in teaching practices not those factors are applied because the teachers had to a lot of time to manage the classroom.